Combining Qualitative Research Perspectives and Methods for Critical Social Purposes: The Neoliberal U.S. Childhood Public Policy Behemoth. Issue 1 (May 2014) - Pérez, Michelle Salazar; Cannella, Gaile S.; Saavedra, Cinthya M.
This article discusses the broad-based use of bricolage to examine the neoliberal childhood policy discourses and forms of implementation that are currently practiced in the United States. Diverse, traditionally marginalized understandings such as Black feminist thought, Chicana feminism, and feminist analysis of capitalist patriarchy are combined with a Deleuze/Guattarian critique of capitalism and qualitative methods of situational analyses. We do this to identify childhood assemblages within the childhood public policy behemoth in the United States and compare these assemblages to capitalism more broadly, including how neoliberal practices are facilitated.